Congenital hypothyroidism: increased incidence in Asian families. Issue 7 (July 1988) - Rosenthal, M; Addison, G M; Price, D A
Abstract : Screening in the North West health region of England showed a significantly higher incidence of congenital hypothyroidism in Asian families–1/918 compared with 1/3391 in non-Asians. This could only in part be explained by consanguinity. No differences were found in birth order, season of birth, gestational age, or birth weight between normal infants and those with congenital hypothyroidism. There was a significantly higher incidence of additional congenital abnormalities (9%) and a significantly increased mortality (5%) in infants with congenital hypothyroidism compared with unaffected infants.